Impact of prior therapy on the efficacy and safety of oral ixazomib-lenalidomide-dexamethasone vs. placebo-lenalidomide-dexamethasone in patients with relapsed/refractory multiple myeloma in TOURMALINE-MM1 - Mateos, María-Victoria; Masszi, Tamas; Grzasko, Norbert; Hansson, Markus; Sandhu, Irwindeep; Pour, Ludek; Viterbo, Luísa; Jackson, Sharon R; Stoppa, Anne-Marie; Gimsing, Peter; Hamadani, Mehdi; Borsaru, Gabriela; et al. (Haematologica, 2017)
Prior treatment exposure in patients with relapsed/refractory multiple myeloma may affect outcomes with subsequent therapies. We analyzed efficacy and safety according to prior treatment in the phase 3 TOURMALINE-MM1 study of ixazomib-lenalidomide-dexamethasone (ixazomib-Rd) versus placebo-Rd. Patients with relapsed/refractory multiple myeloma received ixazomib-Rd or placebo-Rd. Efficacy and safety were evaluated in subgroups defined according to type (proteasome inhibitor [PI] and immunomodulatory drug) and number (1 vs. 2 or 3) of prior therapies received. Of 722 patients, 503 (70%) had received a prior PI, and 397 (55%) prior lenalidomide/thalidomide; 425 patients had received 1 prior therapy, and 297 received 2 or 3 prior therapies. At a median follow up of ~15 months, PFS was prolonged with ixazomib-Rd vs. placebo-Rd regardless of type of prior therapy received; HR 0.739 and 0.749 in PI-exposed and -naïve patients, HR 0.744 and 0.700 in immunomodulatory-drug-exposed and -naïve patients, respectively. PFS benefit with ixazomib-Rd vs. placebo-Rd appeared greater in patients with 2 or 3 prior therapies (HR 0.58) and in those with 1 prior therapy without prior transplant (HR 0.60) versus those with 1 prior therapy and transplant (HR 1.23). Across all subgroups, toxicity was consistent with that seen in the intent-to-treat population. In patients with relapsed/refractory multiple myeloma, ixazomib-Rd was associated with a consistent clinical benefit vs. placebo-Rd regardless of prior treatment with bortezomib or immunomodulatory drugs. Patients with 2 or 3 prior therapies, or 1 prior therapy without transplant seemed to have greater benefit than patients with 1 prior therapy and transplant. TOURMALINE-MM1 registered at clinicaltrials.gov identifier: 01564537.
Keywords: glycin; Drug Resistance, Neoplasm; Kaplan-Meier Estimate; Recurrence; thalidomid; Thalidomide; výsledek terapie; Kaplanův-Meierův odhad; Retreatment; lenalidomid; lidé; mnohočetný myelom; recidiva; Lenalidomide; chemorezistence; Treatment Outcome; Boron Compounds; následné studie; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Follow-Up Studies; opakovaná terapie; dexamethason; Dexamethasone; Glycine; Multiple Myeloma; sloučeniny boru; Humans